(untitled) (Plant Tissue Culture and Biotechnology, 2014)
Heavy metals (HMs) typically inhibit plant growth and development. Only HM accumulators are able to tolerate the presence of these toxic compounds. No studies exist on the response of any orchid cultures to HMs or to nano-particles. In this study, all HMs tested (Al, As, Cd, Cr, Cu, Hg, Ni, Zn) fully reduced neo-PLB growth at or greater than 100 ??. Some neo-PLB growth was observed at 10 and 50 ??, but the levels were significantly lower than the control treatments. Thin cell layers necrosed even at 50 ??, while levels of neo-PLB formation were extremely low at 10 ??. When 100 and 400 mg/l of nano-SiO2 and nano-TiO2 were added to 10 and 50 ?? of all HMs, in a bid to try and mitigate the negative effects of the HMs and improve neo-PLB formation, there was no improvement to neo-PLB formation. Hybrid Cymbidium is thus an extremely HM-sensitive species. Plant Tissue Cult. & Biotech. 24(1): 47-55, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19195